ChemInform Abstract: One‐Step Stereoselective Synthesis of Trisubstituted Monofluoroalkenes from 3, 3, 3‐Trifluoropropionates. Issue 50 (10th December 2013) - Lecea, Mercedes; Grassin, Adrien; Ferreiro‐Mederos, Leticia; Choppin, Sabine; Urbano, Antonio; Carreno, M. Carmen; Colobert, Francoise
Abstract An access towards highly functionalized monofluoroalkenes is presented by the reaction of trifluoropropionates and Li or Mg nucleophiles.